An oxocobalt(IV) complex stabilized by Lewis acid interactions with scandium(III) ions - Pfaff, Florian Felix; Kundu, Subrata; Risch, Marcel; Pandian, Shanthi; Heims, Florian; Pryjomska-Ray, Iweta; Haack, Peter; Metzinger, Ramona; Bill, Eckhard; Dau, Holger; Comba, Peter; Ray, Kallol (Angewandte Chemie. International edition, 2011)
An elusive S=3/2 oxocobalt(IV) complex is stabilized by a Lewis acid interaction with a scandium(III) ion. The CoIV-O-Sc3+ unit, characterized by spectroscopic and DFT methods, is a stronger electron-transfer and H-atom abstraction agent but weaker oxo-transfer agent than the corresponding FeIVO complex (see scheme; L=tris[2-(N-tetramethylguanidyl)ethyl]amine).
First published: 29 December 2010
Gesehen am 05.12.2022